Anticipating Credit Events Using Credit Default Swaps, with An Application to Sovereign Debt Crises - Chan-Lau, Jorge (Washington, D.C. : International Monetary Fund, 2003)
In reduced-form pricing models, it is usual to assume a fixed recovery rate to obtain the probability of default from credit default swap prices. An alternative credit risk measure is proposed here: the maximum recovery rate compatible with observed prices. The analysis of the recent debt crisis in Argentina using this methodology shows that the correlation between the maximum recovery rate and implied default probabilities turns negative in advance of the credit event realization. This empirical finding suggests that the maximum recovery rate can be used for constructing early warning indicators of financial distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet